Equity, Justice, and Quality during the COVID-19 Pandemic Period: Considerations on Learning and Scholarly Performance in Brazilian Schools - Ana Dias; Annibal Scavarda; Augusto Reis; Haydee Silveira; Ana Scavarda (MDPI AG, 2022)
Due to the imperative need for change in habits caused by the COVID-19 pandemic that has plagued the world, this exploratory study plans to analyze the directions taken in teaching activities in public and private schools of the city of Rio de Janeiro (Brazil) and their consequences for learning and scholarly performance concerning elementary and middle schools. In this way, this study verifies through an email questionnaire if there was equality, justice, and quality in teaching methods during the COVID-19 pandemic. The descriptive analysis was carried out based on statistical calculations of quantitative and qualitative variables with various tests, whenever necessary, such as the chi-square, and when inconclusive, Fischer's exact test, Kolmogorov-Smirnov and Shapiro-Wilk, non-parametric Mann-Whitney (when the comparison between two independent groups was mandatory), ANOVA, Kruskal-Wallis, and Friedman test. The results show that teachers tried to interact with students to overcome the problems faced during the COVID-19 pandemic period. Additionally, the study showed that there were differences in scholarly and learning performance, equality, and quality in the types of schools analyzed. This paper will help to fill the literature gap on the subject and will boost ongoing discussion on the inclusion of sustainable concepts in education.